Finance-Led growth regime no Brasil: Estatuto teórico, evidências empíricas e consequências macroeconômicas - Miguel Bruno; Hawa Diawara; Eliane Araújo; Anna Carolina Reis; Mario Rubens (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This paper analyzes the Brazilian growth pattern during the post-liberalization period, emphasizing the structural links between finance and productive capital accumulation. The results indicate a finance-led growth regime in the period 2004-2008, under a very specific financialization process. The first part is a survey of the international literature, which defines the financialization concept and its relevance for understanding Brazilian economic problems. The next part provides a historical overview on the structural changes that made possible the development of financial-led regimes. The paper also applies an empirical analysis of some selected Brazilian macroeconomic indicators.
Keywords: E44; O11; N26; 330; Wirtschaftswachstum; Brasilien